Analysis and Design of Chirped Fiber Bragg Grating for Temperature Sensing for Possible Biomedical Applications - Giovanna Palumbo; Daniele Tosi; Agostino Iadicicco; Stefania Campopiano (My University, 2018)
In this paper, we present the design and analysis of chirped fiber Bragg grating (CFBG) sensors, optimized for temperature measurements. The transfer matrix method has been used to simulate the CFBGs and to study their thermal response. The simulations have been carried out with different temperature profiles in order to understand how the CFBG thermal response varies as a function of the grating design parameters and, thus, to optimize the design for the specific application. Finally, to assess the numerical simulations, a series of experimental tests was performed showing very good agreement.
Keywords: chirped fiber Bragg grating; temperature sensing; biomedical applications; transfer matrix method; optoelectronic sensors